Association of thyroid function with abnormal lipid metabolism in young patients with first-episode and drug naïve major depressive disorder - Hu, Jieqiong; Ji, Yunxin; Lang, Xiaoe; Zhang, Xiang-Yang (Frontiers in Psychiatry, 2023)
Abnormal lipid metabolism in patients with major depressive disorder (MDD) has received increasing attention. The coexistence of MDD and abnormal thyroid function has been intensively studied. Moreover,thyroid function is closely related to lipid metabolism. The aim of this study was to investigate the relationship thyroid function and abnormal lipid metabolism in young patients with first-episode and drug naïve (FEDN) MDD. A total of 1251 outpatients aged 18-44 years with FEDN MDD were enrolled. Demographic data were collected, and lipid and thyroid function levels were measured, including total cholesterol (TC), triglycerides (TG), low-density lipoprotein (LDL-C), high-density lipoprotein (HDL-C), thyroid stimulating hormone (TSH), free triiodothyronine (FT3), free tetraiodothyronine (FT4), anti-thyroglobulin antibodies (TG-Ab) and anti-thyroid peroxidase antibody (TPO-Ab). The Hamilton Depression Scale (HAMD), Hamilton Anxiety Scale (HAMA), and Positive and Negative Syndrome Scale (PANSS) positive subscale were also assessed for each patient. Compared with young MDD patients without comorbid lipid metabolism abnormalities, patients with comorbid lipid metabolism abnormalities had higher BMI values, HAMD score, HAMA score, PANSS positive subscale score, TSH levels, TG-Ab levels, and TPO-Ab levels. Binary logistic regression analysis showed that TSH level, HAMD score and BMI were risk factors for abnormal lipid metabolism. TSH levels were an independent risk factor for abnormal lipid metabolism in young MDD patients. Stepwise multiple linear regression showed that both TC and LDL-C levels were positively correlated with TSH levels, HAMD and PANSS positive subscale scores, respectively. HDL-C levels were negatively correlated with TSH levels. TG levels were positively correlated with TSH and TG-Ab levels and HAMD score. Our results show that thyroid function parameters, especially TSH levels, are implicated in abnormal lipid metabolism in young patients with FEDN MDD.